2011
DOI: 10.1016/s0028-3843(14)60103-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transsphenoidal surgery on glucose homeostasis and insulin resistance in acromegaly

Abstract: We conclude that in acromegalic patients glucose homeostasis alterations and insulin sensitivity can be normalized after transsphenoidal surgery, even if strict biochemical cure criteria are not fulfilled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…A recent Italian epidemiological study also found a 3-fold increase of the prevalence of diabetes in acromegalic patients compared to the Italian population [7]. Furthermore, we also confirmed that at diagnosis most patients with acromegaly exhibit reduced insulin sensitivity, as previously reported [1,3,12,14,24,29] and that patients with diabetes have a more pronounced decrease of β-cell function, suggesting insufficient capacity of pancreatic beta-cells to counterbalance the insulin resistance [1]. This is likely related in part to predisposing factors other than GH hypersecretion, such as a positive familial history for diabetes, aging, or increased BMI.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…A recent Italian epidemiological study also found a 3-fold increase of the prevalence of diabetes in acromegalic patients compared to the Italian population [7]. Furthermore, we also confirmed that at diagnosis most patients with acromegaly exhibit reduced insulin sensitivity, as previously reported [1,3,12,14,24,29] and that patients with diabetes have a more pronounced decrease of β-cell function, suggesting insufficient capacity of pancreatic beta-cells to counterbalance the insulin resistance [1]. This is likely related in part to predisposing factors other than GH hypersecretion, such as a positive familial history for diabetes, aging, or increased BMI.…”
supporting
confidence: 91%
“…This was also confirmed in treated patients by the positive correlation between changes in fasting glucose and in IGF-I but not GH. Thus, we confirm that IGF-I concentration, which reflects integrated 24-h GH secretion [24,35] is better than a fasting GH level as predictor of glucose tolerance status [3,14,24,25,29,36]. This is likely due to the greater stability of circulating total IGF-I.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…This is probably due to adenoma debulking causing improvement in GH and IGF-1 after surgery [51]. This is in contrast to worsening of the parameters after unsuccessful SSA treatment and in line [32,47], and in patients with successful surgery both plasma glucose and insulin sensitivity improve significantly [8,52,53]. To our knowledge, this is the first study to demonstrate that glucose metabolism is significantly improved postoperatively also in the patients that are not cured by surgery.…”
Section: Discussionmentioning
confidence: 79%